1984
DOI: 10.1128/aem.47.5.1113-1117.1984
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water activity and temperature on mycotoxin production by Alternaria alternata in culture and on wheat grain

Abstract: Both water activity (a,) and temperature affected the production of altenuene (AE), alternariol (AOH), and alternariol monomethyl ether (AME) by Alternaria alternata on wheat extract agar and wheat grain. Greatest production of all three mycotoxins occurred at 0.98 'a and 25°C on both substrates. At 0.98 a, and 25°C, a single colony of A. alternata grown on wheat extract agar produced 807 jig of AOH, 603 jag of AME, and 169 jig of AE per ml in 30 days. However, production of all three mycotoxins at 0.95 a, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 28 publications
2
44
0
1
Order By: Relevance
“…However, the aflatoxin contents of the samples stored at 85 Ϯ 2% and 95 Ϯ 2% relative humidity decreased after the 15th day of storage (Tables 1 and 2). The effect on aflatoxin production of the different relative humidity levels was also reported by Magan et al (1984) and Gurses et al (2001). It was reported that the fluctuation in the amount of aflatoxin was caused by the decomposition of chemical structure of toxin and the dominance of other indigenous mold strain during storage (Gurses et al 2001).…”
Section: Aflatoxin Total Formation Potentialsupporting
confidence: 75%
See 1 more Smart Citation
“…However, the aflatoxin contents of the samples stored at 85 Ϯ 2% and 95 Ϯ 2% relative humidity decreased after the 15th day of storage (Tables 1 and 2). The effect on aflatoxin production of the different relative humidity levels was also reported by Magan et al (1984) and Gurses et al (2001). It was reported that the fluctuation in the amount of aflatoxin was caused by the decomposition of chemical structure of toxin and the dominance of other indigenous mold strain during storage (Gurses et al 2001).…”
Section: Aflatoxin Total Formation Potentialsupporting
confidence: 75%
“…Development of fungi is dependent on both abiotic and biotic variables. Perhaps the two most important environmental factors are substrate water activity and temperature (Magan et al 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Fungal growth and mycotoxin production result from the complex interaction of several factors and, therefore, an understanding of each factor involved is essential for understanding the overall process and to predict and prevent mycotoxin development (Chamley et al 1994). Temperature and water activity (a W ) are the primary environmental factors that influence growth and mycotoxin production by several Alternaria species in cereals and oil seeds (Young et al 1980;Magan and Lacey 1984;Torres et al 1992;Etcheverry et al 1994;Magan and Baxter 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Although little is known about the TeA biosynthetic pathway and its regulation mechanisms, it has been previously shown that environmental parameters, such as a w and temperature, influence its accumulation. 25,37,40 This suggests that other stress-related pathways might be connected with its production.…”
Section: Discussionmentioning
confidence: 99%